Strong-Motions From Damaging Moderate Magnitude (5.9 ≥ Mw) Earthquakes in Japan Recorded by K-NET and KiK-net - Dhakal, Yadab P. (Frontiers in Earth Science, 2021)
Strong-motions from 79 moderate magnitude (5.9 ≥ Mw) earthquakes that caused various degrees of impact on humans and built-environment in Japan between 1996 and 2019, after the start of K-NET and KiK-net, are presented. As such, most of the earthquakes occurred beneath the land, and institutes had reported damages from events as small as Mw 4.1. Together, large peak ground accelerations exceeding 500 cm/s2 were recorded during 15 earthquakes, reaching approximately 1128 cm/s2 during one event. Similarly, large peak ground velocities exceeding 30 cm/s were recorded during ten earthquakes, reaching about 76 cm/s to the maximum. Most of the large values aforementioned were recorded within a hypocentral distance of approximately 30 km and on soil site conditions. Intermediate to long-period ground motions are of growing concerns in urban areas located on sedimentary basins with mid-rise and high-rise buildings. The threshold magnitude for the large ground motions at the periods of about 2-5 s is not well understood. In March 2013, the Japan Meteorological Agency introduced four levels of long-period ground motion intensity (LPGMI) based on absolute velocity response spectra (AVRS) between 1.6 and 7.8 s. In the present data set, LPGMI of level 3 (AVRS 50–100 cm/s) and level 4 (AVRS > 100 cm/s) were observed each at a single site from shallow-focus earthquakes of Mw 5.8 and 5.9 at distances of approximately 12 and 15 km, respectively. However, the peak response periods were relatively short (1.6-1.8 s). The data showed that LPGM from moderate earthquakes is of lower concern regarding earthquake early warning at distances beyond 200 km. The 2018 Mw 5.5 North Osaka earthquake, despite the moderate magnitude, caused the loss of six human lives and brought significant damage to buildings and lifelines. Comparing the data with the ground motion prediction equations (GMPEs) and other events suggested that the North Osaka earthquake was probably a higher stress drop event. These moderate earthquakes' observations hinted that the commonly used GMPEs in Japan may not sufficiently grasp these earthquakes' hazards.